Determination of Alkali Content & Total Fatty Matter in Cleansing Agents - Betsy, K. J.; Jilu, Mary; Fathima, Reshma; Varkey , Jaya T. (Asian Journal of Science and Applied Technology, 2021)
Cleaning products play an essential role in our daily lives. By safely and effectively removing soil, germs and other contaminants, they help us to stay healthy, care for our homes and possessions, and make our surrounding more pleasant. Soap is a mixture of sodium salt of various naturally occurring fatty acids. Total alkali and fatty matter contents are the most important characteristics describing the quality of soap and it is always specified in commercial transactions. The main objective of the study is to determine the total alkali content and total fatty matter content of some commonly used toilet and washing soaps.